Suicide risk assessment among psychiatric inpatients: a systematic review and meta-analysis of high-risk categories. Issue 7 (6th September 2017) - Large, M.; Myles, N.; Myles, H.; Corderoy, A.; Weiser, M.; Davidson, M.; Ryan, C. J.
Abstract: Background: The clinical care of psychiatric patients is often guided by perceptions of suicide risk. The aim of this study was to examine the methods and results of studies reporting high-risk models for inpatient suicide. Methods: We conducted a registered meta-analysis according to PRISMA guidelines. We searched for relevant peer-reviewed cohort and controlled studies indexed in Medline, EMBASE and PsychINFO. Results: The pooled odds ratio (OR) among 18 studies reporting high-risk models for inpatient suicide was 7.1 [95% confidence interval (CI) 4.2–12.2]. Between-study heterogeneity in ORs was very high (range 0–94.8, first quartile 3.4, median 8.8, third quartile 26.1, prediction interval 0.80–63.1, I 2 = 88.1%). The meta-analytically derived sensitivity was 53.1% (95% CI 38.2–67.5%, I 2 = 95.9%) and specificity was 84.2% (95% CI 71.6–91.9%, I 2 = 99.9%) with an associated meta-analytic area under the curve of 0.83. The positive predictive value of risk categorization among six cohort studies was 0.43% (95% CI 0.014–1.3%, I 2 = 95.9%). A history of suicidal behavior and depressive symptoms or affective disorder was included in the majority of high-risk models. Conclusions: Despite the strength of the pooled association between high-risk categorization and suicide, the very high degree of observed heterogeneity indicates uncertainty about our ability to meaningfully distinguish inpatients according to suicide risk. The limited sensitivity and low positive predictive value of risk categorization suggest that suicide risk models are not a suitable basis for clinical decisions in inpatient settings.